Czy racjonalne działania zapewniają efektywność? - Haus, Ber (Do the Rational Actions Assure the Effectiveness?, 2005)
In this paper the focus is put on the thesis: "is effectiveness the source of the welfare of nations?" The answer on this questions is it can be, but it is not. The main focus is orientated on national decision making and the relation effectiveness - nationality. So the source of welfare is the issue of considerations. The variety of effectiveness has been proved, dispute of nationality of choice
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 168-175